Comparison of multi-band period-luminosity relations for classical Cepheids in the Magellanic Clouds. Issue 7 (July 2016) - Ngeow, Chow-Choong; Kanbur, Shashi M.
Abstract: The period-luminosity (PL) relation for classical fundamental mode Cepheids (hereafter Cepheids) is an important astrophysical tool in distance scale applications. Because of this, we initiated a program to derive multi-band PL relations with Cepheids in the Large and Small Magellanic Cloud (hereafter LMC and SMC, respectively), as there are ∼⃒ 10 3 Cepheids found in these two nearby galaxies. When compared the slopes of the multi-band PL relations for Cepheids in the LMC and SMC, we found that these PL slopes agree with each others except in the V and J band. We also found an excellent agreement of the PL slopes in Wesenheit function, hence we calibrated the Period-Wesenheit (PW) relation by combining the data from both Clouds, together with an accurate LMC distance based on measurement from late-type eclipsing binaries. Our calibrated Wesenheit function is MW = — 3.314 log( P ) — 2.601.